2017
DOI: 10.1112/s0010437x16008307
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian embeddings of cubic fourfolds containing a plane

Abstract: We prove that a very general cubic fourfold containing a plane can be embedded into a holomorphic symplectic eightfold as a Lagrangian submanifold. We construct the desired holomorphic symplectic eightfold as a moduli space of Bridgeland stable objects in the derived category of the twisted K3 surface corresponding to the cubic fourfold containing a plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…By Proposition 20.11, M 0 (v) gives a descent datum for the stability conditions with central charge in A 2 to some that are generic on all fibers; the associated relative coarse moduli space extends M 0 (v) → S 0 to a proper morphism M(v) → S of algebraic spaces, with all fibers being smooth and projective. Over C 8 , it agrees with the moduli spaces of stable objects constructed by Ouchi in [Ouc17].…”
Section: Proofs Of the Main Resultssupporting
confidence: 82%
“…By Proposition 20.11, M 0 (v) gives a descent datum for the stability conditions with central charge in A 2 to some that are generic on all fibers; the associated relative coarse moduli space extends M 0 (v) → S 0 to a proper morphism M(v) → S of algebraic spaces, with all fibers being smooth and projective. Over C 8 , it agrees with the moduli spaces of stable objects constructed by Ouchi in [Ouc17].…”
Section: Proofs Of the Main Resultssupporting
confidence: 82%
“…injects into cohomology, via the cycle class map. Here, h is the natural polarization and Y ⊂ Z is the lagrangian embedding constructed in [Ouc17].…”
Section: Further Resultsmentioning
confidence: 99%
“…In Section 3 we argue that if Y is Pfaffian then for a general [C] ∈ M , the projection of I C (2) into A ∼ = D(X) is the ideal sheaf of four points in X, again up to a shift. Rather than proving this directly, we observe that if [C] lies over j(y) After the preprint of this paper appeared, Ouchi [11] showed that for a very general Y containing a plane -that is, in the opposite situation to [10] -there is a Bridgeland stability condition on A under which the projection of the skyscraper sheaf O y into A is stable; hence Y embeds as a Lagrangian in a holomorphic symplectic eightfold deformation-equivalent to Hilb 4 (K3). Presumably his eightfold is the limit of Z as Y approaches the locus of cubics containing a plane.…”
Section: Introductionmentioning
confidence: 94%